Do job stress, health, and presenteeism differ between Chinese healthcare workers in public and private hospitals: a cross sectional study. Issue 6 (2nd July 2020) - Yang, Tianan; Ma, Mingxu; Guo, Yina; Li, Yaxin; Tian, Huilin; Liu, Yuanling; Chen, Qian; Zhang, Shiyang; Deng, Jianwei
ABSTRACT: To determine if job stress, health, and presenteeism differ between healthcare workers at Chinese public and private hospitals. This cross-sectional study analyzed the records of 1080 healthcare workers in eastern, central, and western China for the period from January2015 through November2015. Data on challenge stress, hindrance stress, health, and presenteeism were collected. Using univariate and multivariate regression and SPSS, we investigated differences between Chinese public and private hospitals in China. Challenge stress, hindrance stress, and presenteeism, but not health status, significantly differed between healthcare workers at public and private hospitals in China. Challenge stress and hindrance stress were significantly higher in public hospitals, while presenteeism was significantly lower in private hospitals. The significant differences between public and private hospitals are attributable to differences in the business practices and management of public and private hospitals. To achieve successful long-term medical reform in China, the adverse effects of psychosocial factors should be considered in future research plans and policies. Chinese hospitals urgently require improvements in management and leadership. Reform efforts should encompass fields such as management science, psychology, and the behavioral sciences.